2013
DOI: 10.1158/0008-5472.sabcs13-s3-07
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S3-07: Letrozole plus dasatinib improves progression-free survival (PFS) in hormone receptor-positive, HER2-negative postmenopausal metastatic breast cancer (MBC) patients receiving first-line aromatase inhibitor (AI) therapy

Abstract: Introduction Dasatinib inhibits the protein tyrosine kinase, Src, which can support the development of bone metastases in patients with ER+ breast cancer. The primary objective of this study is to determine if letrozole plus dasatinib increases the clinical benefit rate (CBR) (CR+PR+SD ≥6mo) in first-line MBC patients compared with letrozole alone. Secondary objectives include overall response; progression-free survival; time to treatment failure (TTF); and toxicity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…While the PFS difference was not significant in overall study population, a higher CBR in the dasatinib arm and higher PFS in patients with symptomatic bone metastasis (HR = 0.68) suggested that dasatinib may have efficacy in a subset of patients [65]. In contrast, a randomised phase II first-line study (NCT00696072) suggested in an exploratory analysis that the addition of dasatinib to letrozole may improve PFS (median 20.1 vs. 9.9 months, HR 0.69) [66]. It remains to be seen if Src is a viable target to enhance endocrine responsiveness.…”
Section: Agents Targeting Src Kinasementioning
confidence: 99%
“…While the PFS difference was not significant in overall study population, a higher CBR in the dasatinib arm and higher PFS in patients with symptomatic bone metastasis (HR = 0.68) suggested that dasatinib may have efficacy in a subset of patients [65]. In contrast, a randomised phase II first-line study (NCT00696072) suggested in an exploratory analysis that the addition of dasatinib to letrozole may improve PFS (median 20.1 vs. 9.9 months, HR 0.69) [66]. It remains to be seen if Src is a viable target to enhance endocrine responsiveness.…”
Section: Agents Targeting Src Kinasementioning
confidence: 99%
“…Among the ten phase 2 studies included in this report, the 6 evaluating epidermal growth factor receptor/ERB family inhibitors (gefitinib [47,48], AZD8931 [49], and MM-121 [50]) or various antibodies (ganitumab [51] and AS14012 [52]) demonstrated disappointing efficacy (Table 3) [47][48][49][50][51][52][53][54][55][56][57]. However, four phase 2 randomized studies of endocrine therapy in combination with a targeted agent generated promising clinical data; these studies involved the cyclin-dependent kinase (CDK) 4/6 inhibitor PD0332991 (palbociclib; TRIO-18/PALOMA-1) [54,55], the SRC tyrosine kinase inhibitor dasatinib (NCT00696072) [57], the mTOR inhibitor everolimus (TAMRAD) [53], and the histone deacetylase (HDAC) inhibitor entinostat (ENCORE 301) [56].…”
Section: Phase 2 Studiesmentioning
confidence: 99%
“…However, four phase 2 randomized studies of endocrine therapy in combination with a targeted agent generated promising clinical data; these studies involved the cyclin-dependent kinase (CDK) 4/6 inhibitor PD0332991 (palbociclib; TRIO-18/PALOMA-1) [54,55], the SRC tyrosine kinase inhibitor dasatinib (NCT00696072) [57], the mTOR inhibitor everolimus (TAMRAD) [53], and the histone deacetylase (HDAC) inhibitor entinostat (ENCORE 301) [56].…”
Section: Phase 2 Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…dasatinib, saracatinib, KX2-391, and bosutinib) showed promising preclinical and early-phase clinical data. A recently presented phase II trial of da-satinib in combination with letrozol in metastatic breast cancer not only showed a reduced percentage of patients with a T-score < -1.5 but also a significantly longer progression-free survival (PFS) in the combination arm compared with letrozol alone [60]. A phase II trial investigating bosutinib, which inhibits the Src/Abl tyrosine kinase as well as many other kinases, showed promising antitumor activity as single agent as well; however, no consistent changes in the levels of bone turnover markers were seen [61].…”
Section: Future Perspectivesmentioning
confidence: 99%